Long term prognosis and cardiovascular complications of patients with systemic sclerosis-related cardiomiopathy. (14th October 2021) - Stronati, G; Ribichini, F; Benfaremo, D; Dichiara, C; Casella, M; Dello Russo, A; Guerra, F; Moroncini, G
Abstract: Background: Both primary (SSc related cardiomyopathy) and secondary cardiac involvement in systemic sclerosis (SSc) is frequent albeit mostly asymptomatic. It represents a negative prognostic factor as almost 25% of SSc patients die from either heart failure or arrhythmia complications. Speckle tracking global longitudinal strain has been proven to be an effective tool both to identify and detect the progress of subclinical heart disease in SSc. The aim of our study was to assess the association between SSc diagnosis and the development of heart failure, pulmonary hypertension, death and need for hospitalization. Materials and methods: We conducted an observational prospective study enrolling all patients with a diagnosis of SSc and no overt cardiac disease. We excluded all patients with a known diagnosis of pulmonary hypertension and atrial fibrillation. For each patient standard echocardiogram and GLS variables were collected. Results: We enrolled 70 patients (61 females, age 56.2±15.4 years) who were followed for a median of 3 years. 68% of the patients had a limited variant of the disease. All-cause mortality was 10% in a 5-year follow-up. During the same period, PH was reached in 13% of all patients, HF in 7% and 18% required at least one hospital admission for cardiovascular causes. A diagnosis of PH was associated with an increased risk of death (ARR 34%; p<0.001) and hospitalization for CV causes (ARR 73%; p<0.001). Moreover, a diagnosis of HF was associated with an increased risk of death (ARR 50%; p<0.001) and hospitalization for CV causes (ARR 61%; p<0.001). A 1% worsening of GLS was associated with an increased risk to develop PH in the following 5 years, both for the left ventricle (OR 1.2; 95% CI: 1.1–1.4; p=0.043) and for the right ventricle (OR 1.1; 95% CI: 1.1–1.3; p=0.045). Conclusions: Pulmonary hypertension and heart failure often occur in patients with cardiac involvement. Both proved themselves to be associated with an increased risk of death and hospitalization for CV causes. Moreover, GLS worsening of both the left and right ventricles may allow us to predict the diagnosis of PH and therefore preemptively start appropriate management. Funding Acknowledgement: Type of funding sources: None.